Adverse respiratory patterns in near-term spontaneously breathing newborn lambs with elevated airway liquid volumes at birth - Davies, I. M.; Crossley, K. J.; McGillick, E. V.; Nitsos, I.; Rodgers, K.; Thiel, A.; Zahra, V. A.; Badurdeen, S.; te Pas, A. B.; Hooper, S. B. (Frontiers in Pediatrics, 2024)
Introduction Recent evidence indicates that respiratory distress (RD) in near-term infants is caused by elevated airway liquid (EL) volume at the beginning of air-breathing after birth. While the adverse effects EL volumes on newborn lung function are known, the effects on respiratory control and breathing patterns shortly after birth (<4 h) are unknown. We investigated the effects of EL volumes on cardiorespiratory function and breathing patterns in spontaneously breathing near-term newborn lambs in the first hours after birth. Methods At 137–8 days gestation (2–3 days prior to delivery; term ∼147 days), sterile surgery was performed on fetal sheep (n = 17) to implant catheters and blood flow probes. At 140 days, lambs were delivered via caesarean section under spinal anaesthesia. Airway liquid volumes were adjusted to mimic the level expected following vaginal delivery (∼10 ml/kg; Controls; n = 7), or elective caesarean section (∼30 ml/kg; elevated airway liquid group; EL; n = 10). Spontaneous breathing and cardiorespiratory parameters were recorded over four hours after birth. Non-invasive respiratory support with supplemental oxygen was provided if required. Results EL lambs required higher inspired oxygen levels (p = 0.0002), were less active (p = 0.026), fed less (p = 0.008) and had higher respiratory morbidity scores than Controls (p < 0.0001). EL lambs also displayed higher rates of breathing patterns associated with RD, such as expiratory braking and tachypnoea. These patterns were particularly evident in male EL lambs who displayed higher levels of severe respiratory morbidity (e.g., expiratory braking) than female EL lambs. Conclusion The study demonstrates that EL volumes at birth trigger respiratory behaviour and breathing patterns that resemble clinically recognised features of RD in term infants.